2002
DOI: 10.1086/338453
|View full text |Cite
|
Sign up to set email alerts
|

Genomewide Linkage Analysis of Celiac Disease in Finnish Families

Abstract: Celiac disease (CD), or gluten-sensitive enteropathy, is a common multifactorial disorder resulting from intolerance to cereal prolamins. The only established genetic susceptibility factor is HLA-DQ, which appears to explain only part of the overall genetic risk. We performed a genomewide scan of CD in 60 Finnish families. In addition to strong evidence for linkage to the HLA region at 6p21.3 (Z(max)>5), suggestive evidence for linkage was found for six other chromosomal regions--1p36, 4p15, 5q31, 7q21, 9p21-2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
55
0
1

Year Published

2004
2004
2016
2016

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 89 publications
(60 citation statements)
references
References 43 publications
4
55
0
1
Order By: Relevance
“…5 Apart from the HLA region, only 5q31-33, with a maximum Zlr ¼ 4.39 (P ¼ 6 Â 10 À6 ), showed genome-wide significant linkage according to standard thresholds. 6 Linkage of CD to this region was originally identified by Greco et al 7 and was also found by Naluai et al 8 and Liu et al 9 Evidence for a risk factor in 2q33 (CELIAC3), likely corresponding to the CTLA4/ICOS genes, comes from association studies mainly in Northern Europe populations. 10 The CELIAC4 locus was mapped to 19p13.1 with a maximum logarithm of odds score ¼ 4.43 in a cohort of 101 affected sib pairs belonging to 82 Dutch families.…”
Section: Introductionmentioning
confidence: 78%
“…5 Apart from the HLA region, only 5q31-33, with a maximum Zlr ¼ 4.39 (P ¼ 6 Â 10 À6 ), showed genome-wide significant linkage according to standard thresholds. 6 Linkage of CD to this region was originally identified by Greco et al 7 and was also found by Naluai et al 8 and Liu et al 9 Evidence for a risk factor in 2q33 (CELIAC3), likely corresponding to the CTLA4/ICOS genes, comes from association studies mainly in Northern Europe populations. 10 The CELIAC4 locus was mapped to 19p13.1 with a maximum logarithm of odds score ¼ 4.43 in a cohort of 101 affected sib pairs belonging to 82 Dutch families.…”
Section: Introductionmentioning
confidence: 78%
“…Chromosome region 1q31 has been implicated in linkage studies in lupus and multiple sclerosis (22)(23)(24). Multiple investigations have suggested linkage for chromosome region 1p36 in lupus (24)(25)(26), celiac disease (27), inflammatory bowel disease (28), and RA (29,30). This region was delineated further in adult RA using a case-control association design of single-nucleotide polymorphisms, resulting in a functional haplotype associated with RA that includes the gene PADI4 (31).…”
Section: Discussionmentioning
confidence: 99%
“…The 12th tube of the reaction identifies the DQB1*02 allele in homozygous, which is an important information, because studies reveal that homozygous haplotype, increases patient´s susceptibility to develop CD (17,21,22) .…”
Section: Determination Of Hla Dq2 and Dq8mentioning
confidence: 99%
“…This is the case of haplotypes DRB1*07-DQA1*0201-DQB1*0202 (DR7-DQ2) and DRB1*11-DQA1*0505-DQB1*03 (DR11-DQ2) (21,25,35) . DQ8 heterodimers are codified by alleles DQA1*0301 and DQB1*0302 and due to bonding unbalance, are transmitted together with allele DRB1*04, forming the haplotype known as DR4-DQ8 (17,36,38) .…”
Section: Introductionmentioning
confidence: 99%